PENGEMBANGAN MODEL LATIHAN LADDER DRILL UNTUK MENINGKATKAN TENDANGAN DOLLYO CHAGI PADA SISWA EKTRAKURIKULER TAEKWONDO DI SMP NEGERI 19 BANDAR LAMPUNG - Lestari, Dinda; Kurniawan, Candra; Siswoyo , Joan; Wicaksono , Lungit (Journal of Physical Activity and Sports (JPAS), 2025)
This study aims to develop a structured and efficient ladder drill training model to improve the Dollyo Chagi kick performance among students participating in Taekwondo extracurricular activities at SMP Negeri 19 Bandar Lampung. The development process followed the ADDIE model, consisting of five stages: analysis, design, development, implementation, and evaluation. The research subjects included twenty Taekwondo athletes from the school's extracurricular program. Model effectiveness was evaluated using psychomotor tests and kick performance measurements. Validation involved experts in Taekwondo, instructional material, and media, resulting in a high validation score of 89%. The paired t-test result (t = 17.98) showed a statistically significant difference between the traditional and the new training model, supporting the model's feasibility and effectiveness. This training approach offers a useful alternative for educators and coaches in enhancing Taekwondo training quality at the school level.